Electronic transport properties of silicon nanowires synthesized by laser ablation - Aslan, Tahir (My University, 2015)
In this thesis electron transport properties of silicon nanowires are studied. The devices are synthesized using a laser ablation technique. The catalysts used in the synthesis are nickel nanoparticles. The silicon nanowires are characterized by scanning electron microscopy, transmission electron microscopy, atomic force microscopy and Raman spectroscopy. Dielectrophoresis is used to align and contact nanowires across two electrodes to create two-terminal devices. In addition four-terminal devices are fabricated using PMMA lift-off based electron beam lithography. Electron transport properties of the fabricated devices have been studied using dc measurement techniques. Resistance of the silicon nanowires has been measured as a function of temperature and magnetic field. These measurements have been accomplished using a Cryogenics system at low temperature, and high magnetic field. Temperature dependent studies reveal that Arrhenius type thermally activated transport behavior is the dominant transport mechanism in measurements at zero magnetic field. Magnetic field dependent measurements show a weak positive linear magnetoresistance. There are also strong oscillations in magnetoresistance curves. The temperature and field independence of the oscillations has been attributed to quantum interference effects.
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science. Johannesburg, 2015.
Keywords: Electron transport.; Silicon.; Nanowires.; Laser ablation.